The Effect of an Educational Curriculum Using the Hanging Ball Device in Learning the Skills of the Smash Serve and the Smash Hit in Volleyball - diman faraj karim sharif (College of Physical Education and Sport Sciences, 2021)
The aim of the research: The educational curriculum has been prepared by using a ball hanging device, the research under, covers the impact of using that device during (serves and spike) skills in Volleyball and compares it with the coach’s program. The researcher showed the significant difference between pre-test and post-test experiments for the educational curriculum. The researcher dissects the similar study that is relative to the new study like the concept of training skill learning. The researcher has used the experimental approach for its relevance to the nature of research. While using the two-group experimental design, one of them is experimental group and the other is control group. the program has been applied on a young volleyball team (Hawler sport club) (2017-2018). The subjects consist of 20 players divided by two groups (experimental and control) randomly each group consists of 10 players. After these steps the researcher was able to find Homogeneity and equivalence in the research subjects. In addition to using the tools and training equipment with research devices while working on the research; several tests took place, some concerning physical ability and some concerning motion. Then the researcher applied the main program for a duration of 6 weeks that consisted of three educational units per week. Each educational unit took a period of 90 minutes. Then the concluding experiment took place. In the end with the help of these experiments the researcher came up with these results. The researcher concluded the following: - The effect of the teaching program with the usage of the ball hanging device to learn skills such as (serve and spike) are positive for beginner players in Volleyball. - The results of the experimental group who carried out the teaching program by using the ball hanging device, came out superior over the control group in both (serve and spike) skills. -The researcher’s best recommendation and advice is while different branches of Physical education applying the educational curriculum they should consider using educational materials. Also, execute researches such as this one in, for different ages, and for both genders.